Análise preliminar da viabilidade da cogeração de energia térmica e elétrica: estudo de caso na UFSCar - Carvalho, Camila Mello de (Universidade Federal de São Carlos, 2024)
This work was motivated by the need to generate renewable energy and reduce greenhouse gas emissions, proposing a preliminary analysis of the technical and economic feasibility of cogeneration of thermal and electrical energy. Energy cogeneration is an efficient approach to maximize the use of energy resources, providing both heat and electricity from a single energy source. Relying on only one source tends to be a more challenging and expensive implementation. Universities in Brazil often serve as examples of implementing new ideas and are significant research centers. This study aimed to conduct a case study at the Federal University of São Carlos (UFSCar) for the implementation of sustainable and innovative practices, seeking to generate economic, environmental, and social benefits while creating a replicable model for other institutions interested in adopting these practices. Additionally, it aims to adopt circular economy principles for solid waste management, given the increasing waste generation. Based on the presented context, the study objectives included evaluating the available technology for energy cogeneration, assessing UFSCar's energy demands, conducting a preliminary analysis of the technical and economic feasibility of implementing a cogeneration system at the university, and identifying the necessary investments, including capital and operational costs, as well as benefits. Recommendations for successful implementation at UFSCar were also proposed. The methods employed in this work involved a literature review on thermal and electrical energy cogeneration, assessing UFSCar's energy demands, a technical feasibility study, including analyses of available cogeneration technologies, an economic analysis, including cost-benefit calculations and sensitivity analysis, followed by the discussion of results and recommendations. The study provides investment figures for the feasibility of thermal and electrical energy cogeneration at UFSCar and practical recommendations for its implementation at the university, including the most suitable technology and necessary facilities. It was concluded that, given the current volume collected, the return relative to the university's demand is low. However, there are several benefits that this technology can provide, in addition to being a replicable model.
Preliminary analysis of the feasibility of cogeneration of thermal and electrical energy: case study at UFSCar
Keywords: Cogeração; Energias renováveis; Resíduos sólidos; Demanda energética; Sustentabilidade; Cogeneration; Renewable energies; Solid waste; Energy demand; Sustainability; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::APROVEITAMENTO DA ENERGIA; ENGENHARIAS::ENGENHARIA QUIMICA